Prodigiosin alkaloids: recent advancements in total synthesis and their biological potential. Issue 15 (25th February 2015) - Nisha; Kumar, Kewal; Kumar, Vipan
<x xml:space="preserve">Abstract</x> The present review article is focused on the medicinal potential and total synthesis of prodigiosins witnessed in the last decade. The aim will be to provide an inspiration to the marvels and pit falls of constructing the polypyrrole heterocycles with in the complex systems.